Pengaruh Penerapan Standar Akuntansi Pemerintahan Berbasis Akrual, Kompetensi Sumber Daya Manusia Dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan (Studi Kasus Pada Organisasi Perangkat Daerah Provinsi Jambi) - Pratama, Edo Agus; Sinadela, Sarah; Gushendarto, Gushendarto (Journal of Economics and Management, 2024)
Jambi Province maintains an opinion from the government's financial reports, namely an unqualified opinion from the 2017-2022 BPK. However, there are several problems at the BPK in managing regional finances, namely the data presented is not appropriate, payment of teacher allowances, management of boss funds and inadequate management of regional receivables. This research aims to determine the effect of implementing accrual-based government accounting standards, human resource competency and internal control systems on the quality of financial reports in the Jambi Province OPD. This research uses quantitative research using primary data in the form of questionnaires using a 1-5 Likert scale and secondary data through documentation. The research method used was a purposive sampling method consisting of 21 OPDs with the number of respondents taken consisting of 3 people per OPD with a sample of 63 respondents. The data analysis method uses descriptive analysis and Structural Equation Modeling (SEM) - Partial Least Square (PLS) analysis using Microsoft Excel and SmartPLS 3 software. The results of the research show that (1) Implementation of accrual-based government accounting standards has a negative and insignificant effect on quality financial reports, (2) Human resource competency has a positive and insignificant effect on the quality of financial reports and (3) The internal control system has a positive and significant effect on the quality of financial reports. The suggestions given are for local governments to further improve employee understanding of accrual-based government accounting standards, provide training to local government officials on a regular and continuous basis and improve SOP’s so that this will have an impact on the quality of financial reports getting better.